Tell this silence : Asian American women writers and the politics of speech - Duncan, Patti, 1970- (University of Iowa Press, 2004)
Tell This Silence by Patti Duncan explores multiple meanings of speech and silence in Asian American women's writings in order to explore relationships among race, gender, sexuality, and national identity. Duncan argues that contemporary definitions of U.S. feminism must be expanded to recognize the ways in which Asian American women have resisted and continue to challenge the various forms of oppression in their lives. There has not yet been adequate discussion of the multiple meanings of silence and speech, especially in relation to activism and social-justice movements in the U.S.I.